Critical View on the Qualification of Electronic Tongues Regarding Their Performance in the Development of Peroral Drug Formulations with Bitter Ingredients - Denise Steiner; Alexander Meyer; Laura Isabell Immohr; Miriam Pein-Hackelbusch (MDPI AG, 2024)
In this review, we aim to highlight the advantages, challenges, and limitations of electronic tongues (e-tongues) in pharmaceutical drug development. The authors, therefore, critically evaluated the performance of e-tongues regarding their qualification to assess peroral formulations containing bitter active pharmaceutical ingredients. A literature search using the keywords 'electronic', 'tongue', 'bitter', and 'drug' in a Web of Science search was therefore initially conducted. Reviewing the publications of the past decade, and further literature where necessary, allowed the authors to discuss whether and how e-tongues perform as expected and whether they have the potential to become a standard tool in drug development. Specifically highlighted are the expectations an e-tongue should meet. Further, a brief insight into the technologies of the utilized e-tongues is given. Reliable protocols were found that enable (i) the qualified performance of e-tongue instruments from an analytical perspective, (ii) proper taste-masking assessments, and (iii) under certain circumstances, the evaluation of bitterness.